The Influence of Green Leadership and Entrepreneurship on the Sustainability of Manufacturing Companies: Mediation of Green Innovation and Knowledge Management - Rasyid, Muhammad Iqbal Abdul; Stepanus, Mone (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2024)
The industrial sector is one of the main contributors to Indonesia's economic development and GDP. However, the growth of the manufacturing industry cannot be separated from negative effects such as waste or emissions produced. The industrial sector is under pressure to immediately reduce the impact of its production emissions and waste on the environment. It needs to transform in a greener direction to improve the company's sustainability performance which consists of 3 aspects, namely economic, environmental, and social. This research will examine the influence of green transformational leadership, knowledge-oriented leadership, and green entrepreneurial orientation on corporate sustainability performance through the mediating role of green innovation and knowledge management processes. The research will be carried out using qualitative methods on 133 manufacturing industries in Indonesia with Structural Equation Modeling (SEM) analysis with the Partial Least Square (PLS) method to test the hypothesis. The results of this research show that the role of mediation has a positive influence on the company's sustainability performance, especially the knowledge management process which can act as a mediator between green transformational leadership, knowledge-oriented leadership, and green entrepreneurial orientation and the company's sustainability performance.